Understanding Consumer Transformation: Dynamics of Innovation and Creativity in SMEs during the Social Media Era at Eid al-Fitr - Sutrisno, Sutrisno; Suherlan; Astutik, Wahyuni Sri (ADMAN: Journal of Contemporary Administration and Management, 2024)
Modern consumers tend to be more digitally connected and have broader access to product information through social media platforms. This has transformed the way consumers search for, choose, and interact with brands and products, significantly influencing consumer purchasing patterns and preferences. This study aims to understand consumer transformation in the dynamics of innovation and creativity in SMEs during the social media era at Eid al-Fitr. The research method used in this study is a literature review with a qualitative approach and descriptive analysis. Descriptive analysis will be used to analyze data taken from 36 articles published between 2013 and 2024 through Google Scholar. The study results show that in facing changes in consumer dynamics influenced by technological innovation and the dominance of social media, especially during the Eid al-Fitr momentum, it is important for SMEs (Micro, Small, and Medium Enterprises) to understand these changes deeply. Consumer transformation is no longer just happening at the level of economic transactions but also involves behavior patterns, preferences, and socially connected interactions increasingly in the digital realm. SMEs need to develop creative and unique marketing strategies, strengthen their presence on digital platforms, leverage technological innovation to expand market reach, pay attention to digital payment integration, and collaborate with fellow SMEs.